Implementing Technology in Upper Elementary English Language Arts - Ashlee Himes, (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
In the education field, we have experienced a shift in how we utilize technology to teach English language arts (ELA) concepts. Technological literacies can easily integrate into curriculum when using the Ohio ELA and Technology Standards to determine the most important objectives and implementation strategies. When educators understand the use and efficacy of technology in ELA instruction and research, they are able to implement new media into reading, writing, and when speaking and listening. Students will be able to naturally learn how to use technology in everyday work. Integrating ELA and technological concepts helps students understand how these medias and modalities can work together. When we implement technology into the umbrellas of ELA, we set students up for success as adults in the 21st century digital world.